Social Media and Sports Marketing as Correlate of Organizing Female Football In North-Central, Nigeria - Falaye Elijah Kayode; Abdulraheem Yunusa Owolabi; Abdulraheem Mulikat (Jurnal MensSana, 2022)
This study examined social media and sports marketing as correlate of organizing female football in North-central, Nigeria. Social media and sports marketing are identified in the literature as contributing factors to development of football. Therefore, there is need for sports administrators to understand this concepts. Objective: To examine the relationship that between social media and sports marketing on organization of female football clubs. Methods: The study adopt descriptive research design of correlation type, with a sampled of 100 respondents purposively selected from three female teams within the study area. Data collected were analysed using Pearson Product Moment Correlation (PPMC). Findings: The finding revealed that a significant relationship exist between use of cell phone, online marketing and mix marketing on organization of female football teams. Conclusion: It is therefore, recommended that digitalized of sports should be adopted as marketing strategy in order to enhance effective organization of female football teams.